A new species and new record of the genus Cumella (Cumacea: Nannastacidae) from Korea - Lee, Chang-Mok; Lee, Kyung-Sook (Zootaxa, 2012)
The new species, Cumella levitergus sp. nov., and the newly recorded species, Cumella arguta Gamô, 1962 are described andillustrated. Cumella scabera Gamô, 1962 is proposed as a synonym of C. arguta in this study. Cumella levitergus is obviouslydistinguished from other known species of Cumella by the combination of the following features: 1) the carapace surface is pit-ted, and has abundant minute alveolate sculpturing, which is round and tightly arranged; 2) the dorsomedian carina is obsoleteand not decorated; 3) the flagellum of the male antenna 2 does not extend past the posterior border of the pleonite 4; 4) the car-pus of pereopod 1 has 3 setae on the inner margin; 5) the carpus of pereopod 2 is shorter than the length of the dactylus; 6) the uropod exopod is 0.65 times as long as the exopod. A key to the Korean Cumella species is also given.Key words: Taxonomy, Cumacea, Nannastacidae, Cumella, new species, synonym, Korea